Trends in ISCCP, MISR, and MODIS cloud‐top‐height and optical‐depth histograms. Issue 4 (28th February 2013) - Marchand, Roger
Abstract: [1] In this article, temporal changes in the Multiangle Imaging Spectro Radiometer (MISR) and Moderate Resolution Imaging Spectrometer (MODIS) joint histograms of cloud‐top height (CTH) and optical depth (OD) over the period 2001 to 2011 are examined. The analysis shows no significant trend in total cloud cover averaged over all oceans between 60°N and 60°S from 2001 to 2011. There are, however, significant trends in the amount of some CTH‐OD histogram components or cloud types. In particular, there was an increase in the amount of cloud with intermediate optical thickness (23 > OD > 3.6) and a decrease in the amount of the most optically thick cloud (OD > 23) over this period. The total cloud amount shows no trend because the increase in the amount of intermediate optically thick clouds is nearly balanced by the decrease in the amount of the most optically thick clouds. This balance is not due to a simple shift toward optically thinner clouds in all regions but has a complex spatial pattern both regionally and vertically. An examination of the geographic distribution of the change shows that the decrease in the amount of the most optically thick cloud occurred primarily in the extratropics. International Satellite Cloud Climatology Project (ISCCP) observations are briefly compared with those from MODIS and MISR. The comparison shows that ISCCP‐retrieved total‐cloud fraction is reasonably robust, but changes in the ISCCP component cloud fractions sometimes show large deviations from those of MISR and MODIS. Key Points: An increase in cloud with OD < 23 but a decrease with OD > 23, 2001 to 2011 Total cloud amount shows no global trend because these two trends nearly balance ISCCP total CF compares well with MISR and MODIS but component CFs don't